2023
DOI: 10.1039/d3fo02225k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chewing ability on in vivo oral digestive characteristics and in vitro gastrointestinal starch hydrolysis of three different types of cooked rice

Hui Yang,
Yingying Hou,
Yujie Pan
et al.

Abstract: Chewing ability has strong effect on the food digestion. However, littler knowledge is known the relationship between food mastication degree and the following gastric emptying. The study was to explore...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…When considering the impacts of individual differences on the digestive process, static simulation methods exhibit diverse variations. Reports indicate that, in studies using static simulation for gastric digestion, even up to four different protein enzyme concentrations have been observed, and, in starch digestion studies, as many as 36 static methods have been reported [ 20 ]. To standardize static simulation research methods, Europe has established a standardized experimental protocol for static oral, gastric, and intestinal simulations with good reproducibility, as depicted in Figure 1 a [ 21 ].…”
Section: In Vitro Digestion Modelsmentioning
confidence: 99%
“…When considering the impacts of individual differences on the digestive process, static simulation methods exhibit diverse variations. Reports indicate that, in studies using static simulation for gastric digestion, even up to four different protein enzyme concentrations have been observed, and, in starch digestion studies, as many as 36 static methods have been reported [ 20 ]. To standardize static simulation research methods, Europe has established a standardized experimental protocol for static oral, gastric, and intestinal simulations with good reproducibility, as depicted in Figure 1 a [ 21 ].…”
Section: In Vitro Digestion Modelsmentioning
confidence: 99%
“…Yang et al [53] found that people with strong chewing ability had a higher rate of saliva secretion, producing more large particles and higher saliva content in the bolus (up to 28%), and a higher degree of oral starch hydrolysis (up to 13.5%). The swallowable bolus in the weak chewing group had larger holes and a looser microstructure with more small rice particles.…”
Section: Effect Of Other Parameters On Digestibilitymentioning
confidence: 99%

Digestibility of starch

Šárka,
Smrčková,
Sluková
2024
Preprint